2017
DOI: 10.1111/jai.13463
|View full text |Cite
|
Sign up to set email alerts
|

Backpack electrofishing effort and imperfect detection: Influence on riverine fish inventories and monitoring

Abstract: Summary An increased electrofishing sampling effort will increase detection probabilities of riverine fishes. In this study, a repeat‐sampling approach was used in small to medium‐sized Ontario (Canada) rivers to estimate: (i) species‐specific detection probabilities of freshwater fishes, (ii) the number of sampling events required to confidently detect species, and (iii) the power of timed‐search surveys to detect future distribution (or occupancy) declines. Wadeable habitats at 36 sites were sampled with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…On the other hand, Baldwin and Aprahamian () showed that sampling focused on salmonids could give good estimates of eel abundance, with catch efficiencies similar to those of other species. Nevertheless, good estimates of occurrence may be difficult to obtain if the abundance is low, and the sampling effort is consequently a key factor for collecting high‐quality presence/absence data (Reid & Haxton, ). The strong effect of temperature on eel occurrence was expected, as eels may be considered a warm‐water species (Tesch, ) and the immigration to fresh water is often initiated at water temperatures of 14–16°C (Knights & White, ; White & Knights, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Baldwin and Aprahamian () showed that sampling focused on salmonids could give good estimates of eel abundance, with catch efficiencies similar to those of other species. Nevertheless, good estimates of occurrence may be difficult to obtain if the abundance is low, and the sampling effort is consequently a key factor for collecting high‐quality presence/absence data (Reid & Haxton, ). The strong effect of temperature on eel occurrence was expected, as eels may be considered a warm‐water species (Tesch, ) and the immigration to fresh water is often initiated at water temperatures of 14–16°C (Knights & White, ; White & Knights, ).…”
Section: Discussionmentioning
confidence: 99%
“…As occurrence data (presence/absence and not density estimates) were used, sampling effort must be controlled for in the statistical model. Logically, the probability of encountering an individual is positively related to sampling effort (Reid & Haxton, ). Although electrofishing in Sweden is standardized, the sampled areas of the sites included varied greatly (ranging from 12 to 700 m 2 , with a mean of 166 m 2 ), and were positively correlated with the river width (Spearman's rho = 0.71, P < 0.001, n = 1917).…”
Section: Methodsmentioning
confidence: 99%
“…Many previous studies have assessed the utility of different sampling gears for stream fish assemblages (Onorato, Angus, & Marion, ; Vincent, ; Yoder & Smith, ). However, to our knowledge, no studies have specifically focused on madtoms, although differences in relative abundance (Neebling & Quist, ; Tiemann & Tiemann, ; Wilkinson, ) and detection probability (Gibson‐Reinemer et al, ; Peoples & Frimpong, ; Reid & Haxton, ) have been noted as part of stream assemblage studies. Herein, gear choice affected the probability that we detected each species during low water conditions, typical of autumn in southeastern streams, having implications for future efforts to describe the presence and absence of these fishes, while explicitly accounting for the size biases related to gear selection.…”
Section: Discussionmentioning
confidence: 99%
“…1998; Vincent, 1971;Yoder & Smith, 1999). However, to our knowledge, no studies have specifically focused on madtoms, although differences in relative abundance (Neebling & Quist, 2011;Tiemann & Tiemann, 2004;Wilkinson, 2012) and detection probability (Gibson-Reinemer et al, 2016;Peoples & Frimpong, 2011;Reid & Haxton, 2017) have been noted as part of stream assemblage studies. Herein, Electrofishing is one of the most common methods for ecological monitoring in wadeable streams, but is occasionally avoided due to increased potential for mortality of threatened and endangered species Note.…”
Section: S Ize S Elec Tivit Ymentioning
confidence: 99%
See 1 more Smart Citation